2006
DOI: 10.1542/peds.2005-2000l
|View full text |Cite
|
Sign up to set email alerts
|

Change in Approach and Delivery of Medical Care in Children With Asthma: Results From a Multicenter Emergency Department Educational Asthma Management Program

Abstract: OBJECTIVES. The Hawaii Child Asthma Research to Elevate Standards (CARES) Program implemented an emergency department (ED)-based education and management program to facilitate National Asthma Education and Prevention Program (NAEPP) guideline understanding among asthmatic children and their families, ED staff, and health care providers.METHODS. The multipronged approach used: (1) 2-phased prospective tracking system of ED asthma patients; (2) ED-based educational intervention for patients/ families; and (3) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 2 publications
1
41
0
Order By: Relevance
“…One solution to this problem is to begin delivery of preventive care in the acute care setting. 17,18 This concept is consistent with the current national emphasis on creating accountable care systems in which all providers are accountable for the quality, cost, and overall care of a group of patients. A previous costeffectiveness analysis performed by these authors suggests that either prescribing or dispensing ICS at the time of ED discharge is more cost-effective than relying on an outpatient visit for ICS initiation and will result in fewer relapse ED visits and fewer subsequent hospitalizations.…”
supporting
confidence: 57%
“…One solution to this problem is to begin delivery of preventive care in the acute care setting. 17,18 This concept is consistent with the current national emphasis on creating accountable care systems in which all providers are accountable for the quality, cost, and overall care of a group of patients. A previous costeffectiveness analysis performed by these authors suggests that either prescribing or dispensing ICS at the time of ED discharge is more cost-effective than relying on an outpatient visit for ICS initiation and will result in fewer relapse ED visits and fewer subsequent hospitalizations.…”
supporting
confidence: 57%
“…27 approaches have reported short-term improvements in outcome measures including lung function, self-efficacy, absenteeism from school, number of days of restricted activity, and number of visits to an emergency department. [33][34][35][36][37] Several reports indicate that the emergency department can be used as a setting for asthma education 38 with the implementation of a standard curriculum 39 and the use of written care plans. 40 However, resources in the emergency department, including time and staff, are not always ideal for providing long-term care and education for asthmatics.…”
Section: Discussionmentioning
confidence: 99%
“…Boychuk et al (44) reported the results of a multipronged approach in Hawaii that included asthma education for ED staff and community-based health care providers in which the proportion of patients using controller medications and possessing a written action plan increased substantially after intervention. Although the best methods of providing education to providers who manage patients during and after an asthma ED visit have not been identified and data showing a definitive relationship between provider education and reduced subsequent asthma ED visits are lacking, more attention to the role of provider education in improving asthma outcomes in high-risk patients is probably warranted.…”
Section: Other Elementsmentioning
confidence: 99%